Sodium-glucose cotransporter 2 inhibition and health benefits: The Robin Hood effect - Sanjay Kalra; Arpit Jain; Jignesh Ved; A G Unnikrishnan (Indian Journal of Endocrinology and Metabolism, 2016)
This review discusses two distinct, yet related, mechanisms of sodium-glucose cotransporter 2 (SGLT2) inhibition: Calorie restriction mimicry (CRM) and pro-ketogenic effect, which may explain their cardiovascular benefits. We term these adaptive CRM and pro-ketogenic effects of SGLT2 inhibition, the Robin Hood hypothesis. In English history, Robin Hood was a "good person," who stole from the rich and helped the poor. He supported redistribution of resources as he deemed fit for the common good. In a similar fashion, SGLT2 inhibition provides respite to the overloaded glucose metabolism while utilizing lipid stores for energy production.